2022
DOI: 10.1002/puh2.18
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based health insurance service utilization and associated factors in Addis Ababa, Ethiopia

Abstract: Introduction Community‐based health insurance (CBHI) scheme is a powerful tool to achieve universal health service coverage by providing financial protection against healthcare costs. Ethiopia introduced CBHI, although its utilization is suspected to be poor. Consequently, this study aimed to assess CBHI service usage and related factors. Methods Six hundred fifty‐two participants were enrolled in this study. Data was collected through a face‐to‐face interview. Results This study indicated that 60% of responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…17 The incidence of CHE is particularly high households with member who have cancer. 18,19 Existing limited studies revealed that more than half of households with members who used medical services for cancer incurred catastrophic health expenditures. For instance, a study conducted in Addis Ababa in 2018 revealed that the incidence of CHE among cancer patients was 74.4%.…”
Section: Introductionmentioning
confidence: 99%
“…17 The incidence of CHE is particularly high households with member who have cancer. 18,19 Existing limited studies revealed that more than half of households with members who used medical services for cancer incurred catastrophic health expenditures. For instance, a study conducted in Addis Ababa in 2018 revealed that the incidence of CHE among cancer patients was 74.4%.…”
Section: Introductionmentioning
confidence: 99%